2013
DOI: 10.17265/1537-1514/2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

E-service Quality Impact on Online Customer’s Perceived Value and Loyalty

Abstract: Although the internet is a popular shopping medium for global consumers, research into the issues of online shopping is still scarce. This study attempts to serve as a basis for internet marketing by employing a holistic model to conceptualize e-service quality. The survey results from 444 college students suggest that the three dimensions of e-service quality: interaction quality, environmental quality, and outcome quality, do have significant impacts on online customer's perceived value and loyalty. Both uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 64 publications
0
6
0
1
Order By: Relevance
“…Anderson and Srinivasan (2003) also argued that e-service quality positively affects customers' e-loyalty. Chen et al (2013) also stated that those customers who were having good perception for service offered using websites are more likely to show higher loyalty. Based on these arguments, we hypothesized that:…”
Section: E-service Quality and E-loyaltymentioning
confidence: 99%
“…Anderson and Srinivasan (2003) also argued that e-service quality positively affects customers' e-loyalty. Chen et al (2013) also stated that those customers who were having good perception for service offered using websites are more likely to show higher loyalty. Based on these arguments, we hypothesized that:…”
Section: E-service Quality and E-loyaltymentioning
confidence: 99%
“…The results of research conducted by previous researchers found that electronic service quality has a significant influence on customer value Chinomona et al (2014), customer satisfaction (Raza et al, 2020), and customer loyalty (Asgari et al, 2014). However, there are also other research results which find that electronic service quality does not have a significant influence on customer value (Chen et al, 2013), customer satisfaction Candra & Juliani (2018), and customer loyalty (Chang & Wang, 2011).…”
Section: Introductionmentioning
confidence: 91%
“…With the rise of online shopping, previous literature has emphasized the critical role of information quality in influencing consumers' online purchasing behavior. For example, Chen et al [43] discovered that information quality had a positive impact on the utilitarian value of online shoppers. Apart from information quality, quick and efficient service also enhances the perceived utilitarian value for buyers.…”
Section: Perceived Utilitarian Valuementioning
confidence: 99%